2016
DOI: 10.1038/srep19450
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of PRPF31 gene expression by MSR1 repeat elements causes incomplete penetrance in retinitis pigmentosa

Abstract: PRPF31-associated retinitis pigmentosa presents a fascinating enigma: some mutation carriers are blind, while others are asymptomatic. We identify the major molecular cause of this incomplete penetrance through three cardinal features: (1) there is population variation in the number (3 or 4) of a minisatellite repeat element (MSR1) adjacent to the PRPF31 core promoter; (2) in vitro, 3-copies of the MSR1 element can repress gene transcription by 50 to 115-fold; (3) the higher-expressing 4-copy allele is not obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 26 publications
2
48
2
Order By: Relevance
“…The expression of the PRPF31 gene has a continuous distribution in the general population with a threshold for normal retina function, so asymptomatic PRPF31 mutation carriers usually have levels of PRPF31 gene expression above this threshold. 12 It has been postulated that this phenomenon occurs by transcriptional regulation of different modifier genes, as CNOT, 13,14 or recently, by a minisatellite repeat element (MSR1) 15 located in the PRPF31 promoter.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of the PRPF31 gene has a continuous distribution in the general population with a threshold for normal retina function, so asymptomatic PRPF31 mutation carriers usually have levels of PRPF31 gene expression above this threshold. 12 It has been postulated that this phenomenon occurs by transcriptional regulation of different modifier genes, as CNOT, 13,14 or recently, by a minisatellite repeat element (MSR1) 15 located in the PRPF31 promoter.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have shown incomplete penetrance of PRPF31 in causing RP, 7 which is consistent with our RP-F3 family. It was reported that some transcriptional factors, such as the minisatellite repeat element (MSR1), 8 which is adjacent to the core promoter of PRPF31, and CNOT3 which is a cis-actin transcriptional factor, 9 play an important role in the regulation of incomplete penetrance of PRPF31 via modulating its mRNA transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, SVs can potentially provide a deeper understanding of how gene expression in complex genetic disease can affect disease etiology, duration, progression and patient outcomes (Feuk et al, 2006). SVs have been implicated in many complex diseases including retinitis pigmentosa (MSR1) (Rose et al, 2016), Alzheimer's (TOMM40) (Lyall et al, 2013), frontotemporal dementia (C9orf72) (DeJesus-Hernandez et al, 2011;Renton et al, 2011), and other neurodegenerative diseases (Beck et al, 2013). The ability of SVs to alter gene expression is likely dependent on their location within and around the gene or intergenic region, with their effects occurring via several mechanisms including, influencing the binding of regulatory elements that determine transcription, mRNA splicing and processing, genome folding and higher order structure, and translation (Roses et al, 2016).…”
Section: Structural Variantsmentioning
confidence: 99%
“…Since SVs can exhibit a range of regulatory effects that can impact levels of gene expression and potentially the phenotype, it is essential that these regions are also properly characterized. For example, a microsatellite repeat element in the promotor region of PRPF31 (precursor mRNA-processing factor 31) results in some mutation carriers developing retinitis pigmentosa, whilst others remain asymptomatic (Rose et al, 2016). The length of this SV was shown to impact the penetrance of the mutation by suppressing transcription of this region by 50-115-fold, resulting in haploinsufficiency (Rose et al, 2016).…”
Section: Structural Variantsmentioning
confidence: 99%
See 1 more Smart Citation